Chromosomal aberrations in infective hepatitis - Matsaniotis, N. (1970)
Structural chromosomal aberrations, in the form of breaks, were found in a significantly higher proportion of bone marrow cells in patients with infective hepatitis than in controls. These anomalies were observed during the first and third weeks after the onset of jaundice but had subsided by the sixth week. Chromosomal aberrations did not appear to be related to the severity of infective hepatitis or to the sex or age of the patients. The distribution of chromosomal abnormalities did not appear to be random; they were observed predominantly in the A(2) and B(4-5) series. Since no abnormalities were detected in the G-group chromosomes, no evidence in support of a relationship between infective hepatitis and Down's syndrome was obtained. Numerical chromosomal aberrations were not observed, nor was any evidence obtained that mitotic activity of bone marrow cells is suppressed in patients with infective hepatitis.